Targeting condom distribution at high risk places increases condom utilization-evidence from an intervention study in Livingstone, Zambia - Sandøy Ingvild; Zyaambo Cosmas; Michelo Charles; Fylkesnes Knut (BMC, 2012)
Abstract Background The PLACE-method presumes that targeting HIV preventive activities at high risk places is effective in settings with major epidemics. Livingstone, Zambia, has a major HIV epidemic despite many preventive efforts in the city. A baseline survey conducted in 2005 in places where people meet new sexual partners found high partner turnover and unprotected sex to be common among guests. In addition, there were major gaps in on-site condom availability. This study aimed to assess the impact of a condom distribution and peer education intervention targeting places where people meet new sexual partners on condom use and sexual risk taking among people socializing there. Methods The 2005 baseline survey assessed the presence of HIV preventive activities and sexual risk taking in places where people meet new sexual partners in Livingstone. One township was selected for a non-randomised intervention study on condom distribution and peer education in high risk venues in 2009. The presence of HIV preventive activities in the venues during the intervention was monitored by an external person. The intervention was evaluated after one year with a follow-up survey in the intervention township and a comparison township. In addition, qualitative interviews and focus group discussions were conducted. Results Young people between 17-32 years of age were recruited as peer educators, and 40% were females. Out of 72 persons trained before the intervention, 38 quit, and another 11 had to be recruited. The percentage of venues where condoms were reported to always be available at least doubled in both townships, but was significantly higher in the intervention vs. the control venues in both surveys (84% vs. 33% in the follow-up). There was a reduction in reported sexual risk taking among guests socializing in the venues in both areas, but reporting of recent condom use increased more among people interviewed in the intervention (57% to 84%) than in the control community (55% to 68%). Conclusions It is likely that the substantial increase in reported condom use in the intervention venues was partially due to the condom distribution and peer education intervention targeting these places. However, substantial changes were observed also in the comparison community over the five year period, and this indicates that major changes had occurred in overall risk taking among people socializing in venues where people meet new sexual partners in Livingstone. Trial registration ClinicalTrials.gov NCT01423357.